Toxicity of insecticide quinalphos-based Kinalux 25EC on fingerling climbing perch (Anabas testudineus): Brain cholinesterase and growth inhibitions - Nguyen Van Cong; Tran Hoang Kha; Bui Thi Bich Hang; Duong Tri Dung; Tran Sy Nam (Case Studies in Chemical and Environmental Engineering)
This study aims to determine median lethal concentration (LC50) and effects at sublethal levels of quinalphos on brain cholinesterase (ChE) and growth of fingerlings climbing perch (Anabas testudineus). Results showed that LC50-96 h was 1.88 mg L−1. Brain ChE activity was significantly inhibited at concentration of 10 % LC50-96h or higher up to the end 96 h of exposure. In the growth experiment, specific growth rate was inhibited 48.0 % and 34.8 % at treatment 10 % and 20 % LC50-96h, respectively while feed conversion ratio elevated to 164.5 % control at treatment 10 % and to 132.3 % at treatment 20 % LC50-96h. Survival rates were 86 % at 10 % LC50-96h and 34.7 % at 20 % LC50-96h. The study indicated that quinalphos is highly toxic for the climbing perch leading to potential health risk for this species living in rice fields of the Lower Mekong Delta. Monitoring and controlling quinalphos levels in aquatic environments are important acts to mitigating its adverse impacts on aquatic organisms. Promoting the use of less toxic or biodegradable pesticides is urgently needed.